Japan : Spillover Report for the 2011 Article IV Consultation and Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
Japan's position is one of the largest and richest economies in the world. Tokyo as a financial marketplace is not a major intermediator of global capital flows. The current macroeconomic environment is conducive to spillovers being larger than captured by the empirical analysis. Apart from heading off tail risks, fiscal consolidation in Japan would have medium to long-term benefits for its partner countries. Exchange rate-related spillovers on foreign financial markets are found to be small and depend partly on policy developments abroad.